A Narrative Literature Review on Oral Fluency and Language Use in EFL Classroom Group Work - Ishfaque Ahmed Abbasil; M. Anthony, Elizabeth (Development in Language Studies, 2022)
This paper examines the available literature to discuss the impact of group work on oral fluency and language use in EFL classrooms. This narrative review analysed the data from two digital databases, Google Scholar and Science Direct, from the years 2018 to 2022. The findings of the data show that group work is almost a part of all modern student-centred approaches; the students learn more and feel comfortable while learning in a student-centred environment. Though very effective, the modern methods of student-centred approaches for developing the speaking skills of EFL learners need more attention for their implementation in the Pakistani context. Furthermore, the review also brings into focus the popularity of Communicative Language Teaching (CLT) in EFL contexts for developing communicative competence among EFL learners.